KEABSAHAN AKTA OTENTIK YANG DIBUAT OLEH NOTARIS PENGGANTI YANG PARA PIHAKNYA ADALAH KELUARGA NOTARIS YANG DIGANTIKAN - Huduri, Andi Nurlaila Amalia (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Substitute Notaries and Notaries have the same in terms of authority, obligations, and responsibilities, as well as the prohibitions that apply to the Notary Public also apply to the Notary Substitute. As in the case of making an authentic deed based on Article 15 paragraph (1) of the UUJN, as well as with the Notary Substitute, nothing is different in terms of its authority, as long as it is not excluded by the Law. Likewise with the prohibition that applies to the Notary also applies to the Notary Substitute, one of the core discussion in this paper is that a Notary in making a deed is prohibited from making it for the Notary himself, a marriage-bound spouse, or someone who has a blood related relationship, a straight down line of ties, to the top, and the line to the side with the Notary. But what about the deed made by a Surrogate Notary at the request of the family of the Notary he replaces, if the Surrogate Notary does not have blood ties with the Notary he has replaced. In UUJN itself, which is a guideline for all Notaries, there are no specific rules or implicit or explicit rules governing the validity and position of the deed made by the Substitute Notary whose parties are the replaced Notary's family.Notaris maupun Notaris Pengganti memiliki kesamaan dalam hal kewenangan, kewajiban, serta tanggungjawab, begitupun dengan larangan yang berlaku pada Notaris berlaku juga untuk Notaris Pengganti. Seperti hal dalam membuat akta otentik berdasarkan Pasal 15 ayat (1) UUJN, begitupun dengan Notaris Pengganti, tidak ada yang berbeda dalam hal kewenangannya, selama tidak dikecualikan oleh UU. Begitupun dengan larangan yang berlaku bagi Notaris berlaku juga bagi Notaris Pengganti, salah satunya inti pembahasan dalam tulisan ini ialah seorang Notaris dalam membuat akta dilarang membuatkan untuk Notaris itu sendiri, pasangan terikat perkawinan, atau orang yang mempunyai pertalian sedarah, garis pertalian lurus ke bawah, ke atas, serta garis ke samping dengan Notaris tersebut. Namun bagaimana halnya dengan akta yang dibuat oleh seorang Notaris Pengganti atas permintaan keluarga Notaris yang digantikannya, jika Notaris Pengganti tersebut tidak memiliki ikatan darah dengan Notaris yang digantikannya. Dalam UUJN sendiri yang merupakan pedoman untuk semua Notaris belum ada aturan khusus atau yang tertuang secara implisit maupun eksplisit yang mengatur tentang keabsahan dan bagaimana kedudukan atas akta yang dibuat oleh Notaris Pengganti yang para pihaknya adalah keluarga Notaris yang digantikan.